Irradiation testing of enhanced uranium oxide fuels. (March 2019) - Insulander Björk, Klara; Kelly, Julian F.; Vitanza, Carlo; Drera, Saleem S.; Holcombe, Scott; Tverberg, Terje; Tuomisto, Harri; Wright, Jonathan; Sarsfield, Mark; Blench, Trevor; Yang, Jae Ho; Kim, Hyun-Gil; et al.
Highlights: Irradiation testing of uranium oxide fuel enhanced with Cr, SiO2 /TiO2 and ThO2 . Irradiation testing of cladding coated with (Fe, Cr, Al) and (Cr, Al) alloys. All tested materials perform as expected, or better. Lowered fuel temperatures observed for fuel enhanced with Cr microcell structure. Unexpectedly low temperatures observed for SiO2 /TiO2 and 40% ThO2 enhanced fuel. Abstract: Enhanced uranium oxide fuel types are being tested in the Halden Research Reactor in Norway with the aim is to assess the effect that these enhancements have on fuel performance. Fuel temperatures, rod pressures and dimensional changes are being monitored online and an extensive post-irradiation examination programme is planned. Preliminary data show that fuel centerline temperatures can be lowered by addition of ThO2 to the fuel matrix, or by incorporating Cr or SiO2 -TiO2 as a network structure within the fuel. In parallel, two types of cladding coatings are tested in order to investigate their in-core properties. No abnormal behaviour has been noted during the first 100 days of irradiation.